Comparative moves: The pursuit of value and belonging in transnational migration toward a “better life” - Simoni, V.; Voirol. J.; Hjalmarson, E. (Ethnic and Racial Studies, 2025)
Moving beyond comparison as a method that juxtaposes community-based case studies, this article explores how migrants with different backgrounds and trajectories themselves deploy comparison in their everyday lives and decision-making. To do so, it examines Cuban and Ecuadorian migrants’ comparative appraisal of different places, values, and visions of a “better life”, shedding new light on the motives, stakes, and effects of their endeavors. The proposed approach advances understandings of how migrants cope with the dominant comparative scripts and hierarchies that migration activates, notably by either conforming to, subverting, or unraveling them. Also highlighted are comparison’s entanglements with questions of choice, belonging, and its experiential and emotional effects, including the suffering it elicits. A multi-dimensional exploration of how comparison plays out among migrants opens research avenues related to transnational living and people’s pursuits of a “better life”, while also raising ethical and epistemological questions for comparative research on migration and beyond.